Public sector revenue Principles, policies, and management - Asquer, Alberto 1973- (Routledge, 2018)
In this time of acute financial pressure on public budgets, there is an increasing interest worldwide in alternative ways for governments to raise money, and how public authorities can develop the capacity to administer revenues efficiently and effectively. Taxation, the primary source of public revenue, is exposed to various threats, while alternative sources of public revenues have much potential but are rarely carefully designed and harnessed.